Implementation Analysis of Prevention and Infection Control in Datu Beru Takengon Hospital - Irwandi Irwandi; Arifah Devi Fitriani; Juliandi Harahap (Newinera Publisher, 2022)
The incidence of HAIs is also associated with high rates of morbidity and mortality in hospitals. 37,000 deaths were recorded in Europe and 99,000 deaths in the United States due to HAIs, 18.5% in Latin America, 23.6% in Asia and 29.3% in Africa. Infection at Datu Beru Hospital Takengon. The type of research is descriptive qualitative. This research was conducted at Datu Beru Takengon Hospital, Jalan Qurrata Aini Kebayakan, Nunang Antara, Bebesen, Central Aceh Regency, Aceh. There were 12 informants in this study. The results showed that from interviews with key informants and supporting informants, the implementation had been running according to existing standards, although there were still some shortcomings. The conclusion of the study was that there were shortcomings from the 11 components of standard precautions: health workers did not use PPE according to the area and indications, hand washing compliance was not up to standard, some still wore jewelry, did not carry out 5 moments, facilities and infrastructure for hand washing were not adequate, room flow was not up to standard. PPI because there are some rooms that are still old buildings, waste sorting and transportation are correct, but the disposal of infectious waste still uses a third party because Datu Beru General Hospital does not yet have an independent incinerator, sorting and management of linen and laundry are good but the distribution and transportation of linen is still using the same and open trolley, Health checks and immunizations for hospital staff have not been carried out regularly.